ANALYSIS OF THE NON-LINEAR MECHANICAL RESPONSE IN SHEAR OF WOVEN FABRIC REINFORCED COMPOSITE (Glass/Polymer matrix) UNDER MONOTONIC LOADING (Sciences & Technologie. B, Sciences de l'ingénieur, 2005)
This paper considers the analysis of the non-linear mechanical response of a laminateconstituted of 12 layers of glass fiber/ epoxy resin tested in uniaxial tension until the failure atconstant imposed displacement rates.The non linearity observed of mechanical behaviour in shear under uniaxial tension for thespecimens oriented at 45° tested "test at 45°" has "plastic" nature.The law exponentiel proposed for the tangent shear modulus has plastic nature and refersto the plastic flow of the matrix. This model precises the evolution of the tangent shearmodulus depending on the mechanical state characterized by the shear strain.